2012
DOI: 10.1002/app.38026
|View full text |Cite
|
Sign up to set email alerts
|

Influence of laminate thickness reduction on the deformation mechanism of coextruded multilayered PC/PMMA films

Abstract: The influence of the morphology of multilayered composites of poly(methyl-methacrylate) (PMMA) and polycarbonate (PC) fabricated by layer multiplying coextrusion technique on their mechanical and especially their micromechanical deformation behavior was investigated. Electron microscopic studies revealed that the PC/PMMA multilayered composites have a well-oriented, uniform, and continuous layered architecture. With decreasing layer thickness of each polymer in the composite, the elongation at break of the fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…4 where peaks identified after Gaussian fit are close to the aforementioned wavenumbers, i.e. 1830 cm − 1 (C_O anti-symmetric stretching mode); 1750 cm −1 , 1650 and 1680 cm −1 (C_O symmetric stretching mode); 1560 cm −1 (COO − anti-stretching mode); 1450 and 1460 cm −1 (O\CH 3 asymmetric bending mode); 1340 and 1360 cm −1 (COO − symmetric stretching mode); 1250 cm −1 (C\O vibration mode of C\O\C); 980 and 990 cm −1 (C\O vibration mode of C\O\C); 810 and 820 cm −1 (C\H out-of-plan deformation) [17][18][19][20][21][22][23]. There are some very minor shifts from the standard peaks as the deposited PMMA films are amorphous.…”
Section: Ftir Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…4 where peaks identified after Gaussian fit are close to the aforementioned wavenumbers, i.e. 1830 cm − 1 (C_O anti-symmetric stretching mode); 1750 cm −1 , 1650 and 1680 cm −1 (C_O symmetric stretching mode); 1560 cm −1 (COO − anti-stretching mode); 1450 and 1460 cm −1 (O\CH 3 asymmetric bending mode); 1340 and 1360 cm −1 (COO − symmetric stretching mode); 1250 cm −1 (C\O vibration mode of C\O\C); 980 and 990 cm −1 (C\O vibration mode of C\O\C); 810 and 820 cm −1 (C\H out-of-plan deformation) [17][18][19][20][21][22][23]. There are some very minor shifts from the standard peaks as the deposited PMMA films are amorphous.…”
Section: Ftir Spectroscopymentioning
confidence: 99%
“…During measurement, the detector is in line with the sample at its back side. Our focus on the FTIR spectrum is in the range of: 1790-1870 cm −1 (C_O anti-symmetric stretching mode), 1725-1765 cm −1 and 1650-1680 cm −1 (C_O symmetric stretching mode); 1560 cm −1 (COO − anti-stretching mode); 1440-1460 cm −1 (O\CH 3 asymmetric bending mode); 1310-1400 cm −1 (COO − symmetric stretching mode); 960-1000 cm − 1 (C\O vibration mode of C\O\C), 805-890 cm −1 (C\H out-of-plan deformation) [17][18][19][20][21][22][23].…”
Section: Molecular Structurementioning
confidence: 99%
“…In fact, such a concept has already been proposed and employed in industry. 3,4 In this study, we propose a new method for producing transparent sheets in which PMMA is localized at the surface of a miscible blend of PC and PMMA. It has recently been reported that a polymer with a broad molecular weight distribution exhibits molecular weight segregation in the molten state under large temperature gradients.…”
Section: Introductionmentioning
confidence: 99%